Intersections of (infra)structural violence and cultural inclusion: The geopolitics of minority cemeteries and crematoria provision. Issue 3 (5th March 2021) - Maddrell, Avril; McNally, Danny; Beebeejaun, Yasminah; McClymont, Katie; Mathijssen, Brenda
Abstract : Building on embodied and de‐colonial approaches to geopolitics, this paper examines the relationship between forms of governance in municipal cemetery and crematorium provision and the needs of established minorities, arguing that inadequate infrastructure and services can constitute harm. Crucially, it is contended that forms of governance impact not only on the living, but also on perceptions of the wellbeing of the dead. Grounded in a study of four towns in England and Wales, the paper identifies firstly how intersectional identity fundamentally shapes people's experiences of deathscape governance; secondly, the possibilities of infrastructural benefits of inclusive services; and thirdly, the harms done by non‐inclusive forms of governance, implicit territoriality and inadequate infrastructure. This is evidenced in the negative impact of poor municipal cemetery organisation and management on specific minority groups, such as inadequate burial space, high burial costs, hindrances to timely rituals, and reduced access to services as a result of government austerity measures; as well as protracted local planning processes. The conclusion calls for a wider conceptualisation of necropolitics, based on a critical‐feminist‐decolonial geopolitics of deathscapes in multicultural societies, and offers insights for the practical governance of inclusive cemeteries and crematoria. Abstract : Building on embodied and de‐colonial approaches to geopolitics, this paper examines the relationship between forms of governance in municipal cemetery and crematorium provision and the needs of established minorities, arguing that inadequate infrastructure and services can constitute harm. Crucially, it is contended that forms of governance impact not only on the living but also on perceptions of the wellbeing of the dead. Grounded in four case study towns in England and Wales, the paper identifies first how intersectional identity fundamentally shapes people's experiences of deathscape governance; second, the possibilities of infrastructural benefits of inclusive services; and third, the harms done by non‐inclusive forms of governance, implicit territoriality, and inadequate infrastructure, such as inadequate minority burial spaces, high burial costs, hindrances to timely rituals, and protracted planning processes, as well as reduced access to services as a result of government austerity measures. The conclusion calls for a wider conceptualisation of necropolitics, based on a critical‐feminist‐decolonial geopolitics of deathscapes in multicultural societies.